Modeling of Batch Organic Dye Adsorption Using Modified Metal‐Organic Framework‐5. Issue 11 (19th September 2022) - Dahlan, Irvan; Wan Mazlan, Wan Hamizan; Mulkan, Andi; Zwain, Haider M.; Hassan, Siti Roshayu; Aziz, Hamidi Abdul; Hasan, Harahsheh Yazeed Ahmad; Zekker, Ivar
Abstract: Modeling and simulation of batch adsorption of the organic dye methylene blue (MB) by modified metal‐organic framework‐5 (MOF‐5) were investigated. The reported data on the adsorption of MB dye onto Wells‐Dawson acids (H6 P2 W18 O62 )‐immobilized MOF‐5 were employed. The film‐pore diffusion model was developed based on external mass transfer coefficient and pore diffusion coefficient that govern the mass transfer process in batch organic dye adsorption. Applying the estimated parameters, the MB adsorption by using modified MOF‐5 was examined to evaluate the effects of MOF‐5 modification, initial dye concentration, temperature, and the dosage of adsorbent. The adsorption capacity of modified MOF‐5 (H6 P2 W18 O62 /MOF‐5) was higher than pure MOF‐5. Besides, a lower initial MB dye concentration, higher temperature, and lower adsorbent dosage resulted in higher MB dye adsorption capacity. Abstract : A mathematical model based on a film‐pore diffusion model has been developed to simulate the adsorption of the organic dye methylene blue on a modified metal‐organic framework‐5 (H6 P2 W18 O62 /MOF‐5) adsorbent. The model has been effectively applied to simulate the influence of MOF‐5 modification, initial dye concentration, temperature, and adsorbent dosage.